2020
DOI: 10.1080/0092623x.2020.1787279
|View full text |Cite
|
Sign up to set email alerts
|

Average-Size Erect Penis: Fiction, Fact, and the Need for Counseling

Abstract: Most men believe that the average length of an erect penis is greater than 6 inches (15.24 cm). This belief is due, in part, to several often-cited studies that relied on self-reported measurements, with means of about 6.2 inches (15.75 cm) for heterosexual men and even greater for gay men. These studies suffered from both volunteer bias and social desirability bias. In this review, the combined mean for 10 studies in which researchers took measurements of erect penises was 5.36 inches (13.61 cm; n ¼ 1,629). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…She denied rape or use of foreign object. She described the partner’s genitalia as normal size (12.95–13.97 cm) [ 4 ]. She had three eutocic vaginal deliveries, without severe obstetrics lacerations or heavy bleeding that could let us assume a possible loss of vaginal tissue integrity.…”
Section: Casementioning
confidence: 99%
“…She denied rape or use of foreign object. She described the partner’s genitalia as normal size (12.95–13.97 cm) [ 4 ]. She had three eutocic vaginal deliveries, without severe obstetrics lacerations or heavy bleeding that could let us assume a possible loss of vaginal tissue integrity.…”
Section: Casementioning
confidence: 99%
“…According to human guidelines on priapism, the first corporal aspirated blood gas values show pO 2 > 90 mmHg, pCO 2 < 40 mmHg and pH 7.35-7.4, as cavernous tissue appears to be well-oxygenated in non-ischemic priapism [1][2][3][4][5]. However, because the size of feline penises is significantly smaller than those of canines and humans, it was impossible to aspirate blood from the caverrnosal bodies for gas analysis in this case [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the mean length for self-reported erect penis length has been 6.0–6.4 inches. The combined mean length in 10 studies in which researchers took measurements (of pharmacologically induced full erections) was 5.36 inches, and 5.11 inches in 21 studies of fully stretched penises (King, 2021 ). In a recent study, 10% of sexually experienced men self-reported erect penis lengths of 8 inches or more (and 30.8% reported 7 inches or more).…”
Section: Social Desirability Responding In Sex Researchmentioning
confidence: 99%